Roles of Semaphorin-6B and Plexin-A2 in Lamina-Restricted Projection of Hippocampal Mossy Fibers. - MITCHELL, KEVIN (Society for Neuroscience, 2010)
Hippocampal mossy fibers project preferentially to the proximal-most lamina of the suprapyramidal region of CA3, the stratum lucidum, and proximal-most parts of the infrapyrmidal region of CA3c. Molecular mechanisms that govern the lamina-restricted projection of mossy fibers, however, have not been fully understood. We previously studied functions of neural repellent Semaphorin-6A (Sema6A), a class 6 transmembrane semaphorin, and its receptors, plexin-A2 (PlxnA2) and PlxnA4, in mossy fiber projection and have proposed that PlxnA4-expressing mossy fibers are principally prevented from entering the Sema6A-expressing suprapyramidal and infrapyramidal regions of CA3 but are permitted to grow into proximal parts of the regions, where repulsive activity of Sema6A is competitively suppressed by PlxnA2 (Suto et al., 2007Go). In the present study we demonstrate that Sema6B, another class 6 transmembrane semaphorin, is expressed in CA3 and repels mossy fibers in a PlxnA4-dependent manner in vitro. In Sema6B-deficient mice several mossy fibers aberrantly project to the stratum radiatum and the stratum oriens. The number of aberrant mossy fibers is increased in Sema6A;Sema6B double knock-out mice, indicating that Sema6A and Sema6B function additively to regulate proper projection of mossy fibers. PlxnA2 does not suppress the Sema6B response, but itself promotes growth of mossy fibers. Based on these results, we propose that the balance between mossy fiber repulsion by Sema6A and Sema6B and attraction by PlxnA2 and unknown molecule(s) prescribes the areas permissive for mossy fibers to innervate.
PUBLISHED
Keywords: Neurology; Semaphorin-6B; Hippocampal Mossy Fibers